2022
DOI: 10.3389/fneur.2022.953285
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of intracranial aneurysm research from 2012 to 2021: Global productivity and publication trends

Abstract: BackgroundThis study aimed to analyze the global research trends and map the knowledge network of intracranial aneurysm (IA) research in the last 10 years.MethodsPublications related to IA from 2012 to 2021 were retrieved from the Web of Science core collection. Microsoft Excel 2010 and VOSviewer were used to characterize the largest contributors, including authors, journals, institutions, and countries. CiteSpace and VOSviewer were adopted to analyze the trends and knowledge network of IA.ResultsA total of 5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In Supplementary Figure S1, annual publications from China have shown a steady increment since 2011. In addition, our previous bibliometric analysis showed that, from 2012 to 2021, Chinese scholars were active in IA fields, especially after 2015 (13). In addition, we found that the percentage of publications in Stroke, Journal of Neurosurgery, and Neurosurgery (the highest citation journal) by authors from Japan and the United States was much higher than that from China (Supplementary Table S1).…”
Section: Countrymentioning
confidence: 71%
See 1 more Smart Citation
“…In Supplementary Figure S1, annual publications from China have shown a steady increment since 2011. In addition, our previous bibliometric analysis showed that, from 2012 to 2021, Chinese scholars were active in IA fields, especially after 2015 (13). In addition, we found that the percentage of publications in Stroke, Journal of Neurosurgery, and Neurosurgery (the highest citation journal) by authors from Japan and the United States was much higher than that from China (Supplementary Table S1).…”
Section: Countrymentioning
confidence: 71%
“…Previous studies explored the trend of animal models used for Alzheimer's disease (11) and scoliosis (12). In addition, our previous study suggests a future research direction of studying the pathogenesis of IA from the perspective of inflammation-related genes and hemodynamics (13). Therefore, the present bibliometric analysis aimed to summarize the properties of the IA-related animal studies from the Web of Science (WOS) database.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative time zones of the keywords were mapped using COOC, and Figure 9 shows the top 15 high-frequency keywords for 2020-2022. The graph provides an overall picture of changes in the study path (65)(66)(67)(68). The size of the circles next to the keywords represents the number of keyword occurrences.…”
Section: Emerging Trendsmentioning
confidence: 99%
“…Importantly, after the outbreak of the COVID-19 pandemic, research on depression among PLWH needs to be updated and explored further. Thus, in this study, we analyzed depression-related research on HIV/AIDS using the CiteSpace and VOSviewer ( Pan et al, 2018 ; Zhang et al, 2022a , b , c ). This study aims to answer the following research questions.…”
Section: Introductionmentioning
confidence: 99%